Clinical Experience With Perampanel for Refractory Pediatric Epilepsy in One Canadian Center. (August 2017) - Datta, Anita N.; Xu, Qi; Sachedina, Shafina; Boelman, Cyrus; Huh, Linda; Connolly, Mary B.
Perampanel (PER) is a new antiseizure medication that inhibits the α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) class of glutamate receptors. It is important for physicians to be aware of the efficacy and tolerability of new drugs in the postmarketing phase. We performed a retrospective review of our experience with perampanel at BC Children's Hospital. Twenty-four pediatric patients prescribed perampanel from 2014 to 2016 were identified. Fifteen (63%) discontinued perampanel, and 10 (42%) had greater than 50% reduction in seizures. Twelve (50%) had behavioral and 8 (33%) had nonbehavioral adverse events. One-third experienced serious adverse events. One patient experienced oculogyric crisis, which is not previously reported with perampanel. Adverse events were not dose related and were reversible. Possible risk factors for behavioral adverse events include a history of behavioral problems with other antiseizure medications and preexisting behavioral comorbidities. It is important to counsel patients about the potential for serious adverse events, particularly behavioral, when prescribing perampanel.